Manfaat Aktivitas Fisik Teratur Terhadap Perbaikan Fungsi Kognitif Pasien dengan Mild Cognitive Impairment - Rina Amtarina (Fakultas Kedokteran Universitas Riau, 2016)
Regular physical activity have a positive impact on improving cognision for elderly with Mild Cognitive Impairment(MCI). Our aim was to answer a clinical question of the effect exercise for improving cognition. We conducted anEvidence Based Case Report (EBCR) of exercise effects on cogitive outcomes in elderly with MCI. We did electronicsearching on database PubMed, Cochrane Library, ScienceDirect, National Electronic Library for Health, Bandolier,Trip Database and SumSearch for 2004-2014, using keywords and combination of search term(s): AND, OR, brackets.The search found three articles with various strength of evidence. Most of them could prove that regular activity havepositive impact on improving cognision.